A New Data Hiding Algorithm Based on Direction Vector for Digital Images - Tuncer, Turker; Aver, Engin (Ieee, 2015)
Nowadays, data hiding algorithms are widely used These algorithms performance criteria of reliability, capacity, transparency and robustness. Reliability of data hiding algorithms in use today has become the subject of debate. In this study, the vector direction based on a high capacity data hiding algorithm is proposed This process image data hiding algorithm that case gezilerek 3X3 blocks are performed. Each 3x3 block of 4 bits are embedded To reduce the variation in carrier has benefited the edge extraction algorithms. The algorithm used is reliable, less the change in carrier and a high-capacity data hiding algorithm.
23nd Signal Processing and Communications Applications Conference (SIU) -- MAY 16-19, 2015 -- Inonu Univ, Malatya, TURKEY
Keywords: Data Hiding; Steganography; Image Processing; Edge Detector